مظاهر التنوع اللغوي في الإشهار السياحي الرقمي مقاربة سوسيولسانية - ساسي, حورية (جامعة الوادي - University of Eloued, 2019)
أصبح الإشهار جزءا لا يتجزأ من حياة الإنسان؛ فأينما حل وارتحل يجد أمامه خطابا سلطويا؛ يوجهه ويمارس تأثيره عليه؛ وهو بلا منازع من أشهر الوسائل المعبرة عن المواقف والانفعالات النفسية و الاجتماعية والاقتصادية ... للمجتمع، و قد ساهمت التكنولوجيا في تطوير مساره ؛ فأضحى الفضاء الإلكتروني مطمح الشركات والوكالات الناشطة في الترويج لمنتوجاتها وخدماتها؛ مما وسع من دائرة تمرير هذا الإشهار؛ فطورت في خطابها الإشهاري، وفي أسلوب الدعاية الإشهارية؛ لكونه فضاء رحبا يصل لأكبر نسبة من الجماهير، ذات الأصول المتعددة؛ وعليه فإن لغة الإشهار الإلكتروني؛ تكون لغة جامعة للغات العالمية موازاة لطبيعة المتلقي الإلكتروني. Advertising has become an integral part of human life; wherever he traveled, he finds in front of him an authoritative discourse, addressing and exerting an influence on it. It is considered to be one of the most famous means of expressing psychological, social and economic attitudes and emotions, … etc. to society, and technology has contributed to its development course. The electronic space has become the aspiration of companies and agencies active in promoting their products and services, which has expanded the scope of this publicity. It has been developed in its advertising discourse and in the method of advertising publicity, because it is a broad space that reaches the largest rate of audience with multiple origins. Thus, the language of electronic advertising is an international language of languages in parallel to the nature of the electronic recipient. Thus, the language of electronic advertising is an international language of languages parallel to the nature of the electronic recipient.
مقال
Keywords: الإشهار الإلكتروني؛ الإشهار السياحي الإلكتروني؛ التنوع اللغوي؛ الفضاء الإلكتروني؛ المتلقي الإلكتروني; Digital Advertising; Digital Tourism Advertising; Language Diversity; electronic space; electronic recipient